2011
DOI: 10.1186/1471-230x-11-46
|View full text |Cite
|
Sign up to set email alerts
|

Management of esophageal stricture after complete circular endoscopic submucosal dissection for superficial esophageal squamous cell carcinoma

Abstract: BackgroundEndoscopic submucosal dissection (ESD) permits removal of esophageal epithelial neoplasms en bloc, but is associated with esophageal stenosis, particularly when ESD involves the entire circumference of the esophageal lumen. We examined the effectiveness of systemic steroid administration for control of postprocedural esophageal stricture after complete circular ESD.MethodsSeven patients who underwent wholly circumferential ESD for superficially extended esophageal squamous cell carcinoma were enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
149
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(158 citation statements)
references
References 20 publications
3
149
3
1
Order By: Relevance
“…Isomoto et al [54] described seven patients with superficial SCC who underwent completely circumferential ESD. Of the seven patients, four were treated with an 8 wk course of oral prednisolone that was administered at a dose of 30 mg daily on the third post-ESD day and tapered off gradually (30 Administration of oral prednisolone effectively either prevented esophageal stricture or reduced the number of EBD sessions.…”
Section: Management Of Esophageal Stricture After Esdmentioning
confidence: 99%
See 1 more Smart Citation
“…Isomoto et al [54] described seven patients with superficial SCC who underwent completely circumferential ESD. Of the seven patients, four were treated with an 8 wk course of oral prednisolone that was administered at a dose of 30 mg daily on the third post-ESD day and tapered off gradually (30 Administration of oral prednisolone effectively either prevented esophageal stricture or reduced the number of EBD sessions.…”
Section: Management Of Esophageal Stricture After Esdmentioning
confidence: 99%
“…In a retrospective study in 41 patients with esophageal stricture after complete circular or semicircular ESD for esophageal SCCs involving more than threequarters of the lumen, Yamaguchi et al [55] compared an oral prednisolone group with a pre-emptive EBD group. Oral prednisolone was administered as in Isomoto et al [54] 's report. Pre-emptive EBD was started on the third day post-ESD and continued twice weekly for 8 wk.…”
Section: Management Of Esophageal Stricture After Esdmentioning
confidence: 99%
“…Therefore, sufficient preoperative explanation and prevention of stenosis are necessary." And, it is now becoming possible to treat the whole circumference lesion via ESD and to control the stenosis (14). Table 2 shows prevention methods of post-procedural strictures by steroids.…”
Section: Risk and Prevention Of Post-procedural Stenosismentioning
confidence: 99%
“…4) Subcircumferential or circumferential ESD was performed in the clinical setting in patients who were hoped would not have to undergo esophagectomy or patients with severe comorbidities. 12,13) Thereafter, most of these patients required several sessions of dilation because of severe/refractory dysphasia although their preoperative conditions were asymptomatic. Repeated dilation has the potential risk of tears/ perforation, which results in potentially lethal complications and worsens the quality of life (QOL).…”
Section: Endoscopic Treatmentmentioning
confidence: 99%
“…They concluded that oral steroid therapy after EBD is an effective strategy for the management of esophageal strictures after complete circumferential ESD. The local injection of triamcinolone acetonide 18) and other systemic steroid therapies 13) are frequently used to prevent esophageal strictures after ESD. Moreover, ESD for esophageal cancer is generally a more difficult technique as compared to ESD for gastric cancer because the working space is small in esophageal ESD.…”
Section: Endoscopic Treatmentmentioning
confidence: 99%